A scoping review of the Trauma Recovery Center model for underserved victims of violent crime - Annette M. Dekker; Jennifer Wang; Jason Burton; Breena R. Taira (AIMS Public Health)
Victimization in the United States is common and has long lasting negative impacts for individuals, often disproportionately impacting those of color and from low socioeconomic communities. The Trauma Recovery Center (TRC) model aims to provide comprehensive mental health and wrap-around case management services for underserved victims of crime. Following PRISMA-ScR guidelines, we sought to further our knowledge about the impact of the TRC model. Twelve studies met the inclusion criteria. Studies were based at three sites. Access to treatment ranged from 55.7% to 72.3%; treatment completion rates ranged from 40.4% to 43.0%. Individuals who completed mental health services showed improvement in PTSD, anxiety, and depression symptoms, while experiencing lower rates of injury recidivism. Several studies demonstrated improvement in mental health symptoms and social needs in individuals from underserved communities. Researchers should focus on expanding and diversifying upon current knowledge to better understand the impact of the TRC model.